Imaging dynamic changes of an intracellular cysteine pool that responds to the stimulation of external oxidative stress. Issue 7 (4th February 2019) - Chen, Kun; Zhang, Meng; Qi, Yalin; Fan, Jing; Ma, Xiang; Zhu, Hailiang; Qian, Yong
Abstract : A fluorescence-based probe (CyP ) suitable for imaging the dynamic changes of endogenous cysteine activities under external oxidative stress in living cells, nematode, and Arabidopsis thaliana was developed. Abstract : Understanding the dynamic status of intracellular cysteine that responds to the stimulation of external oxidative stress is of great importance to mechanistic studies of cysteine related biology and medicine. However, due to the interference of structural similarity and comparable reactivity of other bio-thiols under physiological conditions, it is exceedingly challenging to develop fluorescent probes with excellent selectivity and sensitivity for the visualization of cysteine activities in an intricate biological context. Herein, we report a new fluorescent probe with an extended coumarin fluorophore, CyP, which displays favorable advantages for intracellular cysteine detection in living cells, and enables effective in vivo visualization of endogenous cysteine activities under external stimuli in live nematodes and plants. In addition, the dynamic changes of the intracellular cysteine pool after exposure to cadmium-induced oxidative stress have been successfully monitored by using this probe in Arabidopsis thaliana, thus providing a valuable diagnostic tool to investigate cysteine functions in a variety of biological phenomena.